Thomas Edison : inventor with a lot of bright ideas - Venezia, Mike. (New York : Children's Press, 2009)
Examines the life and career of American inventor and businessman Thomas Edison, and features cartoon-style illustrations, and reproductions of Edison's sketches and notebooks.
Includes index.
Booklist
Library Media Connection starred
Wilson's Children
5.3
3-6
Keywords: Edison, Thomas A. -- 1847-1931 -- Juvenile literature; Edison, Thomas A. -- 1847-1931.; Edison, Thomas A. -- 1847-1931.; Electrical engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Electrical engineers; Inventors; Electrical engineers -- Biography; Inventors -- Biography